Investigation of the Gas Generation in Lithium Titanate Anode Based Lithium Ion Batteries. Issue 9 (9th July 2015) - Fell, Christopher R.; Sun, Liyuan; Hallac, Peter B.; Metz, Bernhard; Sisk, Brian
Abstract : Lithium titanate (LTO), Li4 Ti5 O12 is a promising material for energy storage due to its high-rate capabilities and safety. However, gas generation, which can be observed under high-temperature operation, present a challenge to the large-scale application of lithium ion batteries made from LTO anodes. Here we analyzed sources of gas generation in an LTO system through isotopic tagging of primary suspected sources of H2 . Specifically, we added small amounts of heavy water (D2 O) to the electrolyte, D2 O to the LTO electrode, or deuterated dimethyl carbonate (DMC) to the electrolyte. Upon cycling, the isotopic tagging method enables the separation of deuterated from non-deuterated gas products using combined gas chromatography and mass spectroscopy (GC/MS) analysis. The results demonstrate that cell performance and generation of H2 are both strongly related to moisture content within the cells. Cells with deuterated DMC in the electrolyte show negligible breakdown as determined by the lack of H-D/D2 gas production when compared to samples that contain D2 O added into the electrode or electrolyte. These results indicate that the primary source of gas generation in LTO-based cells is residual moisture in the electrodes and electrolyte, reinforcing the importance of low-moisture processing conditions for LTO-based lithium ion batteries.